An inclusive approach to designing a multi-epitope chimeric vaccine for Taenia infections by integrating proteomics and reverse vaccinology - Sharma, Swati; Sharan, Ujjawal; Kaur, Rimanpreet; Chaudhary, Anubha; Rawat, Suraj S.; Keshri, Anand K.; Arora, Naina; Prasad, Amit (Frontiers in Tropical Diseases, 2024)
BackgroundSoil- and water-transmitted helminths are a major concern in the developing world due to their high prevalence. More than a quarter of the population were estimated to be infected with helminths in these endemic zones.Research designAn in silico approach was used to design a vaccine construct against the Taenia genus utilizing the proteomic information and evaluation of the construct using immune-informatics.ResultsOur study identified 451 conserved proteins in Taenia spp. using the existing proteome; out of these, 141 were found to be expressed in cysticerci. These proteins were screened for antigenic epitopes and a multi-subunit vaccine was constructed. The constructed vaccine was assessed for its efficacy in mounting the appropriate immune response. Our constructed vaccine showed stability and optimal performance against the TLR 4 receptor, which is reported to be upregulated in Taenia infections in hosts.ConclusionImmune-informatics tools help design vaccines for neglected diseases such as those attributed to helminths, which are known to cause widespread morbidity. Our vaccine construct holds tremendous potential in conferring protection against all Taenia spp. of clinical relevance to human.